Social Media Marketing and Brand Image on Repurchase Intention in Wardah Product - Ramadhania Ramadhania; Hesti Mayasari; Desy Afriani (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
The purpose of this study was to determine and analyze the effect of social media marketing and brand image on repurchase intention. marketing and brand image on repurchase Intention in wardah products at Makeup Holiq in Padang City. The research method used is non probability sampling, namely purpositive sampling so that it is found is observation, questionnaire and literature. The data analysis techniques used are multiple linear regression analysis, t test, F test and coefficient of determination. Based on the results of tests carried out individually found social media marketing variables and the coefficient of determination. and the coefficient of determination. While the F results found that social media marketing and brand image together have a significant effect on repurchase Intention in wardah products in Padang city. While the coefficient of determination determination coefficient is found in the Adjusted R-Square value of 68.3% and the remaining 31.7% is explained by other variables not examined in this study.